Peningkatan Kesadaran Bahaya Asap Rokok Bagi Kesehatan Pada Siswa SMP Negeri 1 Tegal - Agus Susanto; Rosaria Ika Pratiwi; Ahmad Sunardi (Universitas Lancang Kuning, 2020)
Schools as non-smoking areas (KTR) have not been maximized to implement smoking behavior prevention programs for students. The health education requires efforts to strengthen students' knowledge and attitudes about smoking behavior and its dangers to health. This community service (PKM) activity aims to increase students' knowledge and awareness of the dangers of cigarette smoke for health. The main target in this activity is 8th grade and 9th grade j public junior high school students #1 Tegal. This activity was carried out for two days divided into the first day was pretest and on the second day the activity was carried out. Measurement of increasing knowledge is based on the difference between the pretest score and the post test score. The results of the activity showed a significant increase in knowledge and attitudes, which was indicated by a mean pretest score of 10 and a mean posttest score of 12.20. Improvements also occurred in student attitudes, as indicated by the mean pretest value of 62.62 and the posttest value of 67.02.